Lyophilized Fecal Microbiota Transplantation Capsules for Recurrent Clostridium difficile Infection. (4th October 2017) - Dupont, Hebert; Jiang, Zhi-Dong; Alexander, Ashley; Ajami, Nadim; Petrosino, Joseph F; DuPont, Andrew W; Ke, Shi; Jun, Goo; Hanis, Craig
Abstract: Background: Fecal microbiota (FM) transplantation (FMT) is a highly effective treatment of recurrent C. difficile infection (rCDI). We have published data showing efficacy of fresh, frozen and lyophilized donor microbiota administered by colonoscopy. Most groups are moving toward use of frozen product given by enema and in evaluating encapsulated product for oral delivery. Methods: This was a prospective, randomized study of subjects with rCDI (≥ 3 episodes) treated with encapsulated lyophilized FM 100 g given once or 100 g given on two successive days (total 200 g) vs. frozen FM product 100 g given by single retention enema, between March 2015 and February 2017. The clinical outcome was absence of CDI during the 60 days after FMT. The subjects were followed for 6 months for safety. In a subset recipients, microbiome composition by 16S rRNA gene profiling were analyzed on stools obtained pre- and day 2, 7, 14, 30, 60 and 90 days after FMT. Results: A total of 54 subjects were enrolled (37/54; 69% female) with a median age of 71 years (range: 20–97). In the first 14 subjects treated, cure rates for oral capsules 100 g FM was 5/8 (63%) vs. 6/6 (100%) for those receiving 100 g frozen FM by enema ( P = 0.209). In the second phase of the study cure rate for oral capsules 200 g FM was 17/18 (91%) vs. 20/21 (94%) for the subjects treated by enema by 100 g of frozen product ( P = 0.782). No side effects were felt to be related to the procedure or the FMT products were recorded during 6 months follow-up. Two subjects died during follow-up between 3 and 6 months after study due to underlying medical conditions felt to be unrelated to FMT. Microbiota analysis were performed on 40 subjects of which 19/40 (48%) had received capsules. Figure showed that restoration of the intestinal microbiome diversity and Taxa began apparent by 2 days after FMT in both groups and resembled the donor product by 2 weeks with stabilization of the microbiota diversity and Taxa persisting for the 90 days of observation. Conclusion: Administration of encapsulated, lyophilized FM resulted in durable restoration of intestinal microbiome diversity comparable to results seen with frozen product given by enema. Disclosures: All authors: No reported disclosures.